Birth Anomalies and Risk of Childhood CNS Tumors - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at Departments of Neurology, Pediatrics and Neurosurgery, Stanford University, CA linked 3733 patients aged 0 to 14 years with CNS tumors listed in the California Registry to a California birth certificate.